2021
DOI: 10.3390/jcm10040780
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Microbiota Changes in Orthodontic Patients and Effects on Oral Health: An Overview

Abstract: Nowadays, there is a considerable interest to study the biological and microbiological changes that accompany orthodontic treatment. Growing knowledge on oral microbiota allows, day after day, to identify and characterize the microbial arrangements specifically associated with oral and extra-oral conditions. The aim of the present work is to highlight any further correlations between orthodontic appliances and the qualitative and quantitative modifications of the oral microbiota, such as predisposing factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 68 publications
1
43
0
10
Order By: Relevance
“…Furthermore, DS subjects are more predisposed to early-onset and rapidly progressive periodontal diseases, such as gingivitis, localized and generalized juvenile periodontitis and chronic periodontitis [14], further aggravated by their motor disabilities limiting their performance in oral hygiene practices [15].…”
Section: Introduction 1down Syndromementioning
confidence: 99%
“…Furthermore, DS subjects are more predisposed to early-onset and rapidly progressive periodontal diseases, such as gingivitis, localized and generalized juvenile periodontitis and chronic periodontitis [14], further aggravated by their motor disabilities limiting their performance in oral hygiene practices [15].…”
Section: Introduction 1down Syndromementioning
confidence: 99%
“…Oral dysbiosis and poor oral hygiene compromise the health of the peri-implant soft tissues. Furthermore, as in gingivitis and periodontitis, which are diseases responsible for gingival inflammation and bone loss strictly associated with bacterial plaque composition and bone diseases such as osteoporosis [51,52], peri-implant sites can be equally affected by their counterparts as well. These counterparts are called mucositis and peri-implantitis [31,32] which, respectively, lead to inflammation of the mucosa surrounding the abutment and the loss of bone around the fixture, thus compromising the stability of the implant in the bone, which is resorbed and decreased [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Contaldo et al [ 42 ] reported that quantitative changes in plaque in orthodontic patients are observed after just one week after fixation and become more consistent three months after starting treatment. In patients undergoing therapy with fixed appliances, strengthening and regular oral hygiene control are recommended in the first months of treatment.…”
Section: Discussionmentioning
confidence: 99%